Transhumanism as a Challenge to the Medical Doctor-Patient Relation - Miksa, Joanna (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2018)
In this paper I undertake to analyze the way in which the arrival of HETs may influence the therapeutic relationship between the medical doctor and the patient. I begin with presenting he notion of transhumanism, insisting especially on the fact that some of the technologies that can be classified as HETs are already in use. As a result, the traditionally difficult task of defining health and a disease is becoming even more complicated. This circumstance poses the risk that medical doctors in their relationship with the patient, because of the possibilities offered by new technologies, will oscillate in their professional practice between helping the patient to recover and satisfying needs that are not justified by the considerations of health. I will try to show how the therapeutic relationship between the medical doctor and the patient may be transformed because of new technologies by using the example of IVF procedure applied to postmenopausal patients. In order to understand why the relationship between the medical doctors and their patients is so vulnerable in the context of transhumanism, I propose to re-analyze the most basic notions which help us understand the nature of the therapeutic relationship: the status of medicine as contrasted with technology, basic principles of medical ethics, the notion of a disease and an illness.